Use of simulation technology in teaching nursing clinical skills. (28th February 2020) - Kourakos, Michael; Kafkia, Theodora
Nursing education has evolved from being descriptive and more conventional to using state-of-the-art equipment such as simulators and/or computer software. Educational institutions invest in costly technology in order to prepare students for clinical practice while not worrying for patient's safety and confidentiality. On the other hand, educators need to be able not only to use modern technology, but also to prepare appropriate and active learning courses transforming students from passive receptors of knowledge to critical thinkers who can apply their theoretical knowledge in the actual clinical or community setting. The goal of high-fidelity technologies integration into education is to achieve high level and cost-effective care and ultimate patient outcomes.